Aplicación de la NTS TS003 de sostenibilidad para la agencia Sueños y Viajes SAS en la ciudad de Bogotá - Galindo Gómez Kelly Johanna (Universidad Antonio Nariño, 2024)
Sustainability in tourism companies is a challenge today. In Colombia, the implementation of sustainability standards is mandatory since resolution 3160 of 2015. In the case of travel agencies, it corresponds to the Sectoral Technical Standard NTS – TS 003. Its implementation is linked to obtaining/renewing the National Registry of Tourism. However, currently companies still have weaknesses in implementation